A cladistic analysis of the Neotropical genus Sepedonea Steyskal (Diptera: Sciomyzidae) - Marinoni, Luciane; Mathis, Wayne N. (Zootaxa, 2006)
A cladistic analysis of the 13 known species of Sepedonea Steyskal, 1973, is presented and a new species, Sepedonea giovana sp. n., is described. The monophyly of the genus is confirmed, as is the genus’ sister-group relationship to Sepedomerus Steyskal, 1973. The cladistic analysis was done using NONA and a matrix of 27 adult morphological characters, including structures of the male and female terminalia. The relationships in parenthetic notation are: (S. guatemalana (S. veredae (S. lindneri (S. isthmi (S. lagoa ((S. barbosai+ S. canabravana) ((S. neffi (S. giovana+S. guianica))(S. telson (S. incipiens+S. trichotypa))))))))).